Cell kinetics of urethane-induced murine pulmonary adenomata: II, the growth fraction and cell loss factor. - Dyson, P. (Nature Publishing Group, 1976)
Continuous labelling of urethane induced pulmonary adenomata in adult male A2G mice at intervals up to 20 weeks showed that the growth fraction fell progressively from 18% at 7 weeks to 7% at 20 weeks. This fall appears to be wholly responsible for the decrease in production of adenoma cells with age. A fraction labelled mitoses curve was constructed for pulmonary adenomata at 14 weeks post urethane. Only the first peak was apparent, giving median t2 and ts values of 2 and 9 h respectively. The cell cycle time was calculated at 45 h and the growth fraction at 6-2%, whilst the cell loss factor was estimated at 31%. Other cell loss values were calculated from data on the rate of entry into DNA synthesis obtained previously by double labelling. These values remained constant with time at 83-95%, suggesting that cell loss is in some way linked to cell production. However, the development of polyploidy in adenoma cells could not be eliminated. No areas of necrosis were seen in the adenomata at any time although karyorrhexis occurred in isolated cells. The labelling characteristics of alveolar wall cells in the same lung sections as the adenomata did not vary with time and the continuous labelling curve gave a growth fraction of 1-8%, a DNA synthetic time of 10 h and a cell cycle time of 30 h.